Analysis Of Determinat Factors Affecting The Junk Food Diet of Adolescents in Jakarta - Almira Nuraelah; Vivilia Niken Hastuti; Putri Salsabila Sapitri Ritongga (Journal of Global Nutrition, 2025)
Overweight among adolescents is multifactorial, including lack of physical activity and an unbalanced diet. Adolescents tend to follow trends such as consuming junk food without paying attention to nutritional content. This study aims to examine the factors associated with junk food consumption among adolescents in the Jakarta area. This Study is an observational analysis using a cross-sectional research design. A total 130 respondents were obtained using the purposive sampling technique. Data were collected using questionnaires related to respondent characteristics (included gender, age, and pocket money), frequency of junk food consumption was tested using the chi-square test. The results of this tudy indicate that the mmajority of respondents 58,3% often frequently junk food consumption and 41,7% rare frequently junk food consumption. There is significant relationship between gender (p<0.005) and pockey money (p<0.05) with frequency of junk food consumption on adolescents.